AN ANALYSIS OF ONLINE PEER FEEDBACK TO FOSTER STUDENTS' CRITICAL THINKING - Syifaulkaromah Syifaulkaromah; R. Bunga Febriani; Didih Faridah (Journal of English Education Program (JEEP), 2021)
The aims of this study is to find out the students' responses to the practice of peer feedback in online learning and to investigate how online peer feedback foster students' critical thinking. In collecting the data, the study used qualitative method especially case study. Questionnaire and students' peer feedback documentations were the data collection. Purposive sampling was used to select twelve students as participants. Open ended questionnaire and students' peer feedback documentations were the data collection. The writer analysed the students’ responses to the implementation of online learning using percentage computation and interpreted it qualitatively. The students’ peer feedback documentations also analysed by using content analysis. The result indicated that using peer feedback in online learning could improve students’ critical thinking skills which was relevant with Bloom’s Taxonomy. In responding to the second research questions, there were six students who think critically that could be seen from how they criticized the peer’s assignment based on their ability to state opinions clearly and concisely.  Moreover, the most of students agreed that the implementation of online peer feedback was more useful and helped them to improve their writing assignment through giving comments to peers and got comments from peers. Therefore, this research has proved that online peer feedback could foster students’ critical thinking and improved their writing skills especially in the subject Academic Writing.Keywords: Online, Peer feedback, Critical thinking